Prediction of lower limb functional recovery after laminoplasty for cervical myelopathy: focusing on the 10-s step test - Nakashima, Hiroaki (Springer-Verlag, 2012)
OBJECTIVE: Operative decompression is indicated for progressive neurological deterioration in patients with cervical compressive myelopathy (CCM). However, the best timing to ensure clinical recovery has not been determined because of the lack of a suitable method. 10 s step (“step”) test is an easily performed physical test to assess the severity of CCM, particularly for the severity of lower limb dysfunction. The purpose of this study was to analyze the predictive value of preoperative step test results in relation to the results of expansive laminoplasty in patients with CCM. MATERIALS AND METHODS: Clinical and imaging data were prospectively collected from 101 patients who underwent cervical expansive laminoplasty for CCM. The Japanese Orthopedic Association (JOA) score and the lower limb function section of the Japanese Orthopedic Association Cervical Myelopathy Evaluation Questionnaire (JOACMEQ-L) were used to evaluate surgical outcomes. Cutoff value was determined by receiver operating characteristic curve analysis to predict clinical recovery after surgery. JOA recovery rate exceeding 50% was defined as an effective clinical result. The treatment was judged to be effective in 30 patients based on the JOACMEQ-L. The cutoff value of the step test was 14.5 in cases of an effective judgment with JOA and JOACMEQ-L. Multivariate analysis showed that preoperative patient age and duration of symptoms were predictive parameters for effectively judging JOA scores. A preoperative step test result of greater than or equal to 14.5 and male gender were significant predictive parameters for an effective judgment with JOACMEQ-L. CONCLUSIONS: Preoperative step test results significantly reflected the effective results of JOACMEQ-L and were predictive of improved lower limb function after laminoplasty in patients with CCM. Patients with a score of greater than or equal to 14.5 can experience effective lower limb functional recovery.